Next-Generation Sequencing Combined With Conventional Sanger Sequencing Reveals High Molecular Diversity in Actinidia Virus 1 Populations From Kiwifruit Grown in China - Wen, Shaohua; Wang, Guoping; Yang, Zuokun; Wang, Yanxiang; Rao, Min; Lu, Qian; Hong, Ni (Frontiers in Microbiology, 2020)
Kiwifruit (Actinidia spp.) is native to China. Viral disease-like symptoms are common on kiwifruit plants. In this study, six libraries prepared from total RNA of leaf samples from 69 kiwifruit plants were subjected to next-generation sequencing (NGS). Actinidia virus 1 (AcV-1), a tentative species in the family Closteroviridae, was discovered in the six libraries. Two full length and two near full genome sequences of AcV-1 variants were determined by Sanger sequencing. The genome structure of these Chinese AcV-1 variants was identical to that of isolate K75, and consisted of 12 ORFs. Analyses of these sequences together with the NGS-derived contig sequences revealed high molecular diversity in AcV-1 populations, with the highest sequence variation occurring at ORF1a, ORF2 and ORF3, and the available variants clustered into three phylogenetic clades. For the first time, our study revealed different domain compositions in the viral ORF1a and molecular recombination events among AcV-1 variants. Specific RT-PCR assays disclosed the presence of AcV-1 in plants of four kiwifruit species and unknown Actinidia spp. in seven provinces and one city.